Malay and English Language Contact in Social Media Texts in Brunei Darussalam and Malaysia - McLellan, James (Frontiers in Communication, 2022)
This paper focuses on aspects of language contact, specifically Malay and English in the domain of social media. Key components of the theoretical framework are world Englishes being by definition code-mixed varieties, and the complementary notions of nativization (of English) and englishization (of Malay, in this case). Texts examined and analyzed are from public social media sites in the Malay world, mostly Negara Brunei Darussalam (henceforth Brunei) but also Malaysia. Brunei is known for having a very high percentage of social media use per head of population, with especially high levels of use of Instagram and Facebook, as well as discussion forums such as Reddit. In their social media interactions Bruneians and Malaysians have a range of language choices, from monolingual English to monolingual Malay, and varying degrees of code-mixing or translanguaging. Many Bruneians and Malaysians are multilingual, and thus may have more than two languages as resources to draw on. Analysis of threads of discussion forum postings on the same topic demonstrate the multilingual repertoire of participants, for whom any of the available language choices are unmarked. This is in part owing to the use of English as one medium of education alongside Malay: consistently in Brunei since 1985, inconsistently in Malaysia since 1963. The conclusion of the paper raises the question of whether it is valid to posit the language of social media as a new variety comprising both local and global influences and inputs.